2017
DOI: 10.1038/s41598-017-01177-6
|View full text |Cite
|
Sign up to set email alerts
|

Activated hepatic stellate cells secrete periostin to induce stem cell-like phenotype of residual hepatocellular carcinoma cells after heat treatment

Abstract: Some evidences show that residual tumor after thermal ablation will progress rapidly. However, its mechanisms remain unclear. Here, we assessed whether activated HSCs could regulate stem cell-like property of residual tumor after incomplete thermal ablation to promote tumor progression. Human HCC cell lines were exposed to sublethal heat treatment to simulate the peripheral zone of thermal ablation. After residual HCC cells were cultured with conditional medium (CM) from activated HSCs, parameters of the stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Many studies have reported that POSTN secreted by CAFs promoted tumor progression and the CSC-like phenotype 24 , 25 , 35 , 36 , and PTK7 has been shown to be a CSC marker in some tumors 7 , 8 . We efficiently knocked down PTK7 expression in the HN6 and SCC-25 cells and overexpressed PTK7 expression in CAL 27 cells with GFP-tagged lentivirus (Supplementary Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported that POSTN secreted by CAFs promoted tumor progression and the CSC-like phenotype 24 , 25 , 35 , 36 , and PTK7 has been shown to be a CSC marker in some tumors 7 , 8 . We efficiently knocked down PTK7 expression in the HN6 and SCC-25 cells and overexpressed PTK7 expression in CAL 27 cells with GFP-tagged lentivirus (Supplementary Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66][67] Higher expression of Laminin-332 in HCC than in normal or peritumoral tissue, association with metastatic phenotype 68 Periostin Periostin interacts with integrins αvβ3, αvβ5, and α6β4, resulting in the activation Akt/PKB and FAK-mediated signaling pathways as well as increased EGFR activation. [69][70][71] Periostin induces stemness in HCC 78 Periostin is upregulated in multiple cancers including HCC and associated with poor outcomes 72,75,76 Growth factors HGF Binds to its receptor Met, resulting in the activation of multiple kinase pathways such as Erk, Akt, and NF-κB 185,255 Promotes hepatocyte proliferation and survival; in HCC, HGF increases tumor migration, neoangiogenesis, proliferation, 180,183,256,257 and chemoresistance. 17 73 Periostin is upregulated in multiple cancers including HCC and associated with poor outcomes.…”
Section: Extracellular Matrix In the Pme And Tmementioning
confidence: 99%
“…72,75,76 Mechanistically, periostin appears to promote HCC development by inducing angiogenesis 77 and stemness of heat-exposed residual HCC cells. 78 Hyaluronic acid (HA) is a non-sulfated glycosaminoglycan which, like other ECM components, exerts multiple functions that include besides its role as mechanical and lubricating component of ECM also the promotion of wound healing, inflammation and epithelial cell behavior. HA bioactivity is via an Erk/AP-1/ SP1.…”
Section: Extracellular Matrix In the Pme And Tmementioning
confidence: 99%
“…As we described previously [19,20], HCC cells were exposed to sublethal heat stress (IT50, 47 C for 10 min) to simulate the incomplete RFA. Cell growth curves of heat-treated residual HCC cells showed an obvious latency growth and slower proliferation compared with control cells treated by 37 C for 10 min (Figure 1(A)).…”
Section: Hcc Cells Survived Sublethal Heat Treatment Via Autophagymentioning
confidence: 99%